Third Party Embargoes – A Practical Legal Perspective - Murillo Magalhães CARRERA (Revista Jurídica Portucalense, 2024)
The relationship between third party embargoes and the sale in progress has been the subject of a wide doctrinal and jurisprudential debate. In effect, under the terms of number 2 of article 824.º of the Civil Code, assets are transferred free of the guarantee rights that encumber them, as well as of other real rights that have no registration prior to any attachment, attachment or guarantee, with with the exception of those established on a previous date, which take effect in relation to third parties regardless of registration. The number 1 of article 342.º of the Civil Code Procedure stipulates that if the attachment, or any judicially ordered act of seizure or delivery of assets, offends the possession or any right incompatible with the performance or scope of the due diligence, the holder who is not a party to the cause, can assert it, deducting third party embargoes. This time, the present work essentially aims to establish when a third party that is not a party to the executive process, can deduct third party embargoes against the attachment or any judicially ordered act that offends its possession or any other right incompatible with the scope of that diligence. The present work essentially aims to establish when a third party that is not a party to the executive process, can deduct third party embargoes against the attachment or any judicially ordered act that offends their possession or any other right incompatible with the scope of that diligence.